Yukstapozytni types of tumors as a basis journalistic style (based on periodicals end of the twentieth century) - Турчак, Елена Михайловна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In the article yukstapozytni types of tumors as a basis in journalistic style on the material periodicals end of the twentieth century. Attention is drawn to the classification yukstapozytiv meaningfully and to analyze their structure. Clarifies that the largest group is in terms apposition that absolutizes or clarify a concept or phenomenon, giving words new semantic nuances.